De la unidad antifascista a la desunión libertaria - Chris Ealham (Casa de Velázquez, 2011)
This article focuses on the impact of the popular-frontist tactic within the libertarian movement from the coup of July 1936 up to the «May events» of 1937, when the leaders of the CNT and FAI stubbornly defended «democratic collaboration» in a context of antifascist struggle. This policy, so far removed from the traditional revolutionary aspirations of organised anarchism, was accompanied by many changes of direction in the anarchist movement, such as the entry of anarchists in popular-front governments in Catalonia and the Republic, or the bureaucratisation of the libertarian movement. The article analyses the tensions between the governmental role of the anarchist ministers and the popular revolution that followed the military coup of July 1936, and the growing tensions between a radical grass-roots sector of anarchism and the so-called higher committees.